Hormones in HIV- Pregnant Women - Mishra, Dr. Asha; Agnihotri, Dr. Madhuri A.; Ratnani, Dr. Rekha (International Journal of Innovative Research in Medical Science, 2018)
Background - HIV infected pregnant women are placed on antiretroviral drugs for treatment and to avoid maternal to child transmission of HIV. This effect of HIV infection on pregnancy hormones within 24 weeks of pregnancy compare with normal pregnant women. Aims and Objectives - estimate testosterone, Luteinizing hormone (LH), Follicle-stimulating hormone (FSH) and Prolactin (Prl) in HIV pregnant women compare to normal Healthy pregnant women. Result - The level of hormones in normal pregnant women and HIV positive pregnant women. Hormone level in HIV pregnant women were significantly decreased found compare to normal pregnant women. Conclusion: On the basis of our study we concluded that the hormone levels were significantly decreased found in HIV pregnant women due to hormones are affected by HIV / AIDs. The bidirectional interactions between hormones and the immune system contribute to both the outcome of pregnancy and female susceptibility to disease.